Remote Tracking of White-Tailed Sea Eagles from Transbaikalia, Russia: Migration, Wintering, Summer Stay - Oleg A. Goroshko; Ivan S. Zaitsev; Dou Huashan; Yuriy A. Anisimov; Liu Songtao; Sergey V. Pyzhianov (Пернатые хищники и их охрана)
Remote tracking of the White-Tailed Sea Eagle (Haliaeetus albicilla) has not yet been carried out in Transbaikalia (Russia). Four juveniles from two nests (2+2) were tagged on 19/06/2020 in the Selenga River delta, Buryatia (about N 52.21; E 106.45) by GPS/ GSM trackers. Tracker #149 was lost during migration on 05/12/2020 in the western Khangai, Mongolia; #158 was lost during the first wintering 03/01/2021 (most probable migration was unfinished); #156, #157 were lost during third wintering in February-March of 2023. In all cases the signal lost was due to transmitter failure. Data on two autumn migrations is incomplete due to poor tracker condition providing no signal for 3–15 days (#156 in 2022, #157 in 2021).